Chemical Composition and Glycemic Index of Gluten-Free Bread Commercialized in Brazil - Romão, Bernardo (2020)
Nowadays, the world is experiencing an increased demand for gluten-free products associated with the high prevalence of gluten-related disorders (GRD). As this market thrives, bread stands out as the most demanded and consumed product, highlighting the need to evaluate its nutritional quality. In this sense, this cross-sectional study aimed to assess the ingredients, chemical composition, and glycemic index of gluten-free bread (GFB) commercialized nationwide in Brazil. The labels were analyzed according to their ingredients and composition. In addition, centesimal composition analysis (moisture, carbohydrates, protein, ash, lipid, and fiber) was performed using the o cial methods, as well as the in vivo glycemic index. Significant di erences between manufacturing lots of each brand and between di erent gluten-free bread samples were found. There is a mismatch from what is stipulated by the Brazilian legislation between analytical data and the data described on sample labels. Samples showed predominantly refined starch and high glycemic index profile. Most samples (75%, n = 6) of the non-whole gluten-free bread (n = 8) presented high glycemic index (GI). From four whole food/multigrain gluten-free bread samples, three of them (75%) presented medium GI. However, two samples presented GI near the value to be considered high. The results suggest a lack of production control, impairing the gluten-free nutritional label as a reliable information source and tool for dietary control. Therefore, it is necessary to standardize the process of gluten-free bread production and labeling, as well as to improve the nutritional characteristics of these products, aiming the give accurate information to consumers and provide a healthier product beyond the sensory characteristics.